PERSEPSI PESERTA DIDIK TENTANG KETERAMPILAN ATTENDING DALAM PELAKSANAAN KONSELING PERORANGAN OLEH GURU BK (Studi terhadap Peserta Didik Kelas X dan XI di SMA NEGERI 4 BUKITTINGGI) - Sari, Novita - (Bimbingan dan Konseling, 2014)
This research is motivated by the conditions found in the field that the implementation of individual counseling is not good , because it is still the presence of learners who looks anxious , tense and counseling teacher scolding learners . This study aimed to describe : 1 ) Skills attending from the aspects of physical movement , 2 ) Skills attending from the aspects of eye contact , 3 ) Skills attending from the aspects of observing , and 4 ) Skills attending viewed from the aspect of listening. This research is descriptive quantitative . The study population was all students of class X and XI ever implement individual counseling in SMA 4 Bukittinggi , as many as 294 students . The techniques used in sampling are simple random sampling , a total of 33 students who are in class X and XI . The instrument used in this study is a questionnaire , while the data used for the analysis of the formulation of the criterion Sturgess . Results of research on the perception of the students attending skills in the implementation of individual counseling by teachers BK , generally categorized quite well . The results based subvariabelnya , namely 1 ) Skills attending from the aspects of physical motion categorized quite good , 2 ) Skills attending from the aspects of eye contact pretty well categorized , 3 ) Skills attending from the aspects of observing categorized quite well , and 4 ) Skills attending visits from the aspect of observing categorized quite well . Based on the results of the study authors suggested to teachers attending BK in order to apply skills in the implementation of individual counseling to students , so that counseling be delivered more effectively .